2008
DOI: 10.1016/j.jcrs.2007.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront-guided versus wavefront-optimized laser in situ keratomileusis: Contralateral comparative study

Abstract: Although both wavefront-guided and wavefront-optimized LASIK gave excellent refractive correction results, the former induced less higher-order aberrations and was associated with better contrast sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 36 publications
(34 reference statements)
3
50
1
2
Order By: Relevance
“…Our safety results are consistent with those of others, who report a good safety profile with wavefront-optimized laser ablations. [15][16][17]20 To our knowledge, no study reported a loss of 2 or more lines of Snellen visual acuity. However, more attention should be paid to reporting changes in Snellen visual acuity lines, as recommended by Reinstein and Waring 21 and Waring 22 and further noted by Fares et al 18 in their metaanalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our safety results are consistent with those of others, who report a good safety profile with wavefront-optimized laser ablations. [15][16][17]20 To our knowledge, no study reported a loss of 2 or more lines of Snellen visual acuity. However, more attention should be paid to reporting changes in Snellen visual acuity lines, as recommended by Reinstein and Waring 21 and Waring 22 and further noted by Fares et al 18 in their metaanalysis.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a trend towards slightly better performance of wavefront-guided versus wavefront-optimized surgery but no significant differences were noted in the majority of visual and aberration measures. 9 An important qualifier was that their wavefront analysis diameter was 7.0 mm and they state that the biggest differences in measurement occurred in the 6.5-7.5 mm zone. This is unlikely to affect patients with smaller pupils.…”
Section: Discussionmentioning
confidence: 99%
“…Wavefrontoptimized ablations apply a precalculated spherical aberration treatment to produce an aspheric ablation profile. 29 An important factor, which accounts for the increase in spherical aberration, is the loss in ablation energy due to the angle of incidence of pulses in the periphery (ie, the cosine effect, leading to an oval beam of reduced energy on the peripherally sloping cornea). The wavefront-optimized laser profile compensates for this effect by increasing the pulse energy in the periphery.…”
Section: Other Ablation Profilesmentioning
confidence: 99%